2003
DOI: 10.1021/ci034033k
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Experimental Bond Dissociation Energies Using Composite ab Initio Methods and Evaluation of the Performances of Density Functional Methods in the Calculation of Bond Dissociation Energies

Abstract: Composite ab initio CBS-Q and G3 methods were used to calculate the bond dissociation energies (BDEs) of over 200 compounds listed in CRC Handbook of Chemistry and Physics (2002 ed.). It was found that these two methods agree with each other excellently in the calculation of BDEs, and they can predict BDEs within 10 kJ/mol of the experimental values. Using these two methods, it was found that among the examined compounds 161 experimental BDEs are valid because the standard deviation between the experimental an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
114
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(128 citation statements)
references
References 55 publications
13
114
1
Order By: Relevance
“…This was also seen by Senosiain et al and from the results given in the paper of Feng et al We can conclude that only composite methods such as CBS-Q and G3 reproduce the BDE of this radical properly whereas DFT methods seriously overestimate the BDE value. [40,38] Our results are in agreement with other data reported in the literature. DiLabio et al and Li et al also suggested that the B3P86 functional was superior to other functionals for the reproduction of BDEs.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…This was also seen by Senosiain et al and from the results given in the paper of Feng et al We can conclude that only composite methods such as CBS-Q and G3 reproduce the BDE of this radical properly whereas DFT methods seriously overestimate the BDE value. [40,38] Our results are in agreement with other data reported in the literature. DiLabio et al and Li et al also suggested that the B3P86 functional was superior to other functionals for the reproduction of BDEs.…”
supporting
confidence: 93%
“…Golden and co-workers further confirmed that the commonly used B3LYP method is insufficient for an accurate evaluation of BDEs and suggested other hybrid methods such as the KMLYP method, that yield rootmean-square (RMS) deviations that are close to the experimental error bars. [38][39][40] Recently a study appeared by Izgorodina, Coote and Radom on trends in RÀX bond dissociation energies in which some new-generation functionals such as B1B95,MPW1PW91, MPW1B95, BB1K, MPW1 K, MPWB1K and BMK were also tested. They found that in particular the BMK functional is very attractive as it shows the smallest systematic errors in the relative BDEs.…”
Section: Phenanthrene Dibenzoa C H T U N G T R E N N U N G [Cg]phenmentioning
confidence: 99%
“…Frequency calculations were performed to confirm that the geometry was a minimum (zero imaginary frequency). The single point energies were then calculated at the B3P86/6-311++G(d,p) level of theory for molecules 1-5 [25]. Radical Stabilization Energies (RSE) of 4 and 5 were calculated at G3B3MP2 (compound method).…”
Section: Methodsmentioning
confidence: 99%
“…[75] However, does DFT, especially the popular B3LYP, give experimentally accurate kinetic and thermodynamic energies? Recently, many investigations have been devoted to testing the performance of DFT methods for bond dissociation energies, [76] enthalpies of formation, [77] enthalpies of atomization, [78] proton affinities, [79] hydrogen abstraction reactions, [80] radical reactions, [81] weak interactions, [82] S N 2 reactions, [83] pericyclic reactions, [84,85] organic reactions, [86,87] metals, [88] materials, [89] biological applications, and even reactions relevant to astrophysics. [90] This section reviews investigations that give the most reliable quantitative thermochemistries for Diels-Alder and 1,3-dipolar cycloadditions.…”
Section: Quantitative Computation Of Activation Barriers and Reactionmentioning
confidence: 99%